2022
DOI: 10.3389/fmicb.2022.945411
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Fitness Cost of Tn7100, a Novel Integrative and Conjugative Element Conferring Multidrug Resistance in Haemophilus influenzae

Abstract: A multidrug-resistant (MDR) strain of Haemophilus influenzae, Hi-228, with phenotypic resistance toward ampicillin, cefotaxime, chloramphenicol, gentamicin, and azithromycin, was isolated in Oslo, Norway. The strain was part of a clonal outbreak (2016–2017) comprising five ST143 strains with identical resistotypes. Hi-228 carries a novel integrative and conjugative element (ICE), Tn7100, contributing to this remarkable and previously unreported MDR profile. Tn7100 contains the following resistance genes: blaTE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…A similar combination of nonbeta-lactam resistance genes was present in the genomes of two out of 15 Hia isolates (13.3%). These MDR profiles, to the best of our knowledge previously unreported in H. influenzae, suggest the presence of integrative conjugative elements (ICE) acquired through horizontal transfer (Hegstad et al, 2020;Johannessen et al, 2022). The molecular environment of the resistance genes and the presence of mobile genetic elements will be further investigated in a planned future study.…”
Section: Level Spbp3 Low Low High-high-highmentioning
confidence: 84%
“…A similar combination of nonbeta-lactam resistance genes was present in the genomes of two out of 15 Hia isolates (13.3%). These MDR profiles, to the best of our knowledge previously unreported in H. influenzae, suggest the presence of integrative conjugative elements (ICE) acquired through horizontal transfer (Hegstad et al, 2020;Johannessen et al, 2022). The molecular environment of the resistance genes and the presence of mobile genetic elements will be further investigated in a planned future study.…”
Section: Level Spbp3 Low Low High-high-highmentioning
confidence: 84%
“…For quantification of viable cells, the suspensions were diluted to 10 −8 and seeded quantitatively on Colombia agar plates (BBL Colombia agar, Becton Dickinson) with 15 mg/L NAD and 15 mg/L haemin. 8 The agar plates were incubated at 35°C in 5% CO 2 for 48 h, with subsequent determination of cfu/mL by colony counts.…”
Section: Methodsmentioning
confidence: 99%
“… 7 Since the year 2000, NTHi strains resistant to cefotaxime and other extended-spectrum cephalosporins have emerged in several geographical regions and constitute approximately half of the isolates in Japan, 5 , 6 and dissemination of MDR strains with co-resistance to clinically important non-β-lactams such as quinolones, trimethoprim/sulfamethoxazole, tetracyclines and/or macrolides restrict alternative therapeutic options. 6 , 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
“…There are just a handful of studies that investigated ICEs in biofilms. Nevertheless, multiple studies have demonstrated ICEs as the main reservoir for several resistance genes in biofilm-producing species [326][327][328][329][330].…”
Section: Integrative and Conjugative Elements (Ices)mentioning
confidence: 99%